1984
DOI: 10.1002/1097-0142(19840515)53:10<2098::aid-cncr2820531018>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The computed tomography-guided adrenal biopsy: An alternative to surgery in adrenal mass diagnosis

Abstract: A series of 16 patients with adrenal masses were biopsied percutaneously under computed tomography (CT) guidance with 18‐ to 22‐gauge modified Chiba needles. Adrenal adenomas, cysts, metastases, melanoma, and adrenal hemorrhage were identified. Of nine oncologic patients, four had adrenal metastases, while five had other nonmalignant adrenal masses. Thus, an adrenal mass in an oncologic patient is not always metastases. No complications occurred. The diagnostic evaluation of an adrenal mass in selected cases s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
4

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 11 publications
1
11
0
4
Order By: Relevance
“…We found that the sensitivity of TAB, which takes into account the procedure of obtaining the biopsy as well as the pathological diagnosis, was at best 70%. In our study, samples were regarded as sufficient for pathological diagnosis in 88% of the cases reviewed at our institution, which agrees with previously reported adequacy ratings ranging from 67% to 100% 22, 23, 25, 28, 33, 37, 39-41 . In terms of diagnosing malignant disease, but not necessarily establishing the diagnosis of ACC, the sensitivity of TAB increases to 84%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the sensitivity of TAB, which takes into account the procedure of obtaining the biopsy as well as the pathological diagnosis, was at best 70%. In our study, samples were regarded as sufficient for pathological diagnosis in 88% of the cases reviewed at our institution, which agrees with previously reported adequacy ratings ranging from 67% to 100% 22, 23, 25, 28, 33, 37, 39-41 . In terms of diagnosing malignant disease, but not necessarily establishing the diagnosis of ACC, the sensitivity of TAB increases to 84%.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have investigated the complications stemming from this procedure 14, 15, 22-37 . Complication rates ranged from 0 – 12%.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 The primary role of FNA biopsy is to differentiate between adrenal tissue and non-adrenal tissues (eg, metastases or infection). 32,34,36,[37][38][39][40]42 Only 2 studies have reported data on metastatic spread of carcinoma along the needle track. Its usefulness in differentiating adrenal adenomas from adrenal carcinomas is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress in the CT diagnosis for adrenal mass has made it possible to biopsy the adrenal tissue to establish the diagnosis before the operation (Berkman et al 1984). However, in some cases it is still difficult to interpret the histologic In case 2, closely located double adenomas in the unilateral gland, a unique finding in Cushing's syndrome, were not diagnosed preoperatively.…”
Section: Discussionmentioning
confidence: 99%